Visual Arts Tourism in Malaysia: A Literature Review - SER, ShawHong (International Journal of Culture and Art Studies, 2020)
This article documented the development of visual arts tourism as a new field of Malaysia's tourism. Since the new millennium, the union of visual arts and tourism has been celebrated by the Ministry of Tourism, Arts & Culture as a marketing strategy to promote Malaysia as a top-of-the-mind destination art tourism destination. The research result has shown that currently there are three significant visual arts programs which are known as (1) One Malaysia Contemporary Art Tourism, (2) Art Expo Malaysia, and (3) Kuala Lumpur Biennale has been developed along with the government's strategies for partnership between visual arts, tourism and economic development. It is hoped that this paper will provide insights into an understanding of the tourism industry in Malaysia, particularly for visual arts tourism development.